Understanding intimate femicide in South Africa - Mathews, Shanaaz (My University, 2010)
When a woman is killed she is most likely to be murdered by an intimate partner. This form of homicide known as intimate femicide is conceptualised to be the most extreme consequence of intimate partner violence. Not much is known about such killings in South Africa or in other developing settings. This thesis studied intimate femicide using two complimentary studies from two methodological perspectives. The first study was quantitative with the aim of describing the incidence and pattern of intimate femicide in South Africa. The second study used qualitative methods and explored the social construction of the early formation of violent masculinities. Five papers written from these two studies are presented in this thesis. Study one was a retrospective national mortuary-based study and collected data on all female homicides, 14 years and older, who died in 1999 from a stratified, multi-stage sample of 25 mortuaries. Data was collected from the mortuary file, autopsy report, and a police interview. The second study used a cluster of qualitative in-depth interviews with 20 incarcerated men in prison who have been convicted for the murder of an intimate partner, as well as interviews with family and friends of both the perpetrator and the victim. Overall it was found that 50.3% of women murdered in South Africa are killed by an intimate partner, with an intimate femicide rate of 8.8/100 000 and an intimate-femicide suicide rate of 1.7/100 000 females 14 years and older. Blunt force injuries were shown to be associated with intimate killings, while gun ownership was associated with intimate femicide-suicides. vi elevated Blood Alcohol Concentration (BAC) combined with unemployed status was also found to be associated with intimate killings. The qualitative study showed that traumatic childhood experiences such as violent and neglectful parenting practises particularly by mothers made these men feel unloved, inferior and powerless with this found to be a pathway to violent models of masculinity used as a means to attain power and respect. This study shows that such traumatic experiences can lead to a suppression of emotions. It is argued that cognitive dissonance act as a protective mechanism which allows these men to perpetrate acts of violence without consideration of its impact. These findings suggests that intimate femicide is a complex phenomenon with a “web” of associated and mediating factors which all contribute to it excessive levels in South Africa. It shows that intimate femicide is an extension of intimate partner violence and as such has to take into account the unequal gender relations in society. Building gender equity and shifting patterns of femininity and masculinity is a key strategy in reducing this form of violence.
A thesis submitted for the degree Doctor of Philosophy in the Department of Public Health, Faculty of Health Sciences University of the Witwatersrand
Keywords: Femicide; Gender relations